AB0768 Relationship between das28 1.2 and sdai50 responses in rheumatoid arthritis. (23rd January 2014) - Omair, M.; Akhavan, P.; Keystone, E. C.; Xiong, J.; Boire, G.; Pope, J. E.; Thorne, J. C.; Hitchon, C. A.; Haraoui, B.; Tin, D.; Weber, D. A.; Bykerk, V. P.; et al.
Abstract : Background: An essential element in the treat to target strategy is modification of treatment in the absence of achieving a target response by 12 weeks. A change in the Disease Activity Score (DAS28 ESR) of 1.2 and Simplified Disease Activity Index (SDAI) of 50% (SDAI50 based on a ACR20) are possible response measures (RM). Objectives: To characterize patients (pts) failing to respond to either RM and determine a relationship between the two. Methods: The study was carried out on the Canadian Early Arthritis Cohort (CATCH) - a multicentre early arthritis RA cohort comprising 1953 pts with disease of <12 months. We evaluated 419 biologic naive pts who had complete records to evaluate their DAS28 (ESR) and SDAIs at Baseline and 12 weeks. We included only pts who initiated treatment with methotrexate as monotherapy or in combination with conventional DMARDs. We included patients failing or achieving either response measure at 12 weeks without a change in therapy. Differences in patient characteristics failing the RM were calculated using the Man Whitney U test or Chi-square test as required with P<0.05 (2 sided). Results: The cohort comprised 74.9% females, mean age: 52.6 years, mean disease duration: 5.7 months. Baseline (BSL) disease characteristics included a mean tender joint count: 9.0, swollen joint count: 8.2, DAS28: 5.2, HAQ: 1.1, SDAI: 29.7, ESR: 27.2, and CRP: 14.4. Of 419 pts evaluated, 198 pts failed to achieve a DAS28 1.2 and 206 pts failed to achieve a SDAI50 by 12 weeks. A strong relationship was observed between DAS28 1.2 and SDAI50 non-responders (Kappa 0.66) and Spearman Correlation (0.66) (p<0001). Of pts failing SDAI50, 19.2% achieved a DAS28 1.2 response, while of pts failing a DAS28 1.2 response, 16.6% pts achieved a SDAI50 response. At BSL and 12 wks, DAS28 was higher in SDAI50 non-responders than DAS1.2 non-responders while DAS28 was higher in DAS28 1.2 responders compared to SDAI50 responders. DAS28 and ACR core set measures at BSL and 12 wks were markedly higher in pts failing SDAI50 but achieving DAS28 1.2 compared to those achieving SDAI50 but failing DAS28 1.2 (p<0.0001). These data are consistent with a higher probability of achieving a DAS28 1.2 response at higher disease activity compared to the SDAI50 response, while SDAI50 is achieved more frequently than DAS28 1.2 with lower disease activity. Conclusions: SDAI50 and DAS28 1.2 RM are well correlated although at high disease states the likelihood of achieving an SDAI50 is lower than achieving a DAS28 1.2, while the reverse is true at lower disease states. Disclosure of Interest: M. Omair: None Declared, P. Akhavan: None Declared, E. Keystone: None Declared, J. Xiong: None Declared, G. Boire: None Declared, J. Pope: None Declared, J. Thorne: None Declared, C. Hitchon: None Declared, B. Haraoui: None Declared, D. Tin: None Declared, D. Weber: None Declared, V. Bykerk Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since inception of CATCH. As of 2011, further support was provided by Hoffman-LaRoche Limited, United Chemicals of Belgium (UCB Canada Inc.)., Bristol-Meyers Squibb Canada Co., Abbvie Inc., and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.).